The effectiveness of Ibis Paint X through project-based learning on learning outcomes in exploring primary and secondary colors - Dani, Anika Rahma; Nurharini, Atip (Jurnal Prima Edukasia, 2026)
The less-than-optimal learning outcomes of students in the Gatot Subroto Cluster serve as the background for this research. The purpose of this study is to analyse the effectiveness of digital media using Ibis Paint X within the Project-Based Learning (PjBL) model. The research employed a quantitative experimental design with a true experimental approach, using cluster random sampling. Research instruments included observations, questionnaires, and tests. Data analysis was performed using inferential statistics to test the research hypotheses. The results indicated a significant difference in learning outcomes between the group utilizing Ibis Paint X based on the PjBL model and the group using conventional media. The average N-gain scores for the experimental and control classes were 59.8% (moderately effective) and 32.1% (ineffective), respectively. In conclusion, Ibis Paint X media integrated with the PjBL model significantly affects student learning outcomes. This approach can be applied by teachers as a viable strategy to improve academic results.